Corporate Social Responsibility Collection and Distribution Strategy at the National Board of Zakat, Republic of Indonesia - Reno Ardianto (ITQAN: Journal of Islamic Economics, Management, and Finance, 2026)
This study aims to analyze the Corporate Social Responsibility (CSR) fundraising and distribution strategies implemented by the Indonesian National Zakat Agency (BAZNAS) and to explore collaborative practices between CSR and Zakat in supporting community empowerment. Using a descriptive qualitative approach based on literature, this study utilizes primary data in the form of official BAZNAS documents and secondary data from relevant literature published over the past five years. The study results indicate that BAZNAS has integrated a modern fundraising approach, strengthened institutional relationships with companies, and a tiered monitoring system to maintain transparency in CSR collection. On the distribution side, the distribution and utilization patterns of CSR funds are designed to address the needs of Mustahiq outside the scope of Ashnaf Zakat, while simultaneously supporting sustainable programs based on the SDGs. Although BAZNAS's CSR contribution is still relatively small compared to the national potential, the positive growth trend each year opens up opportunities for broader synergy between corporate CSR and Zakat management. This study recommends strengthening CSR and Zakat literacy among companies, innovating program designs based on Mustahiq needs, and optimizing digitalization to improve accountability. These findings are expected to serve as a practical reference for BAZNAS and companies in optimizing the role of CSR to support sustainable development in Indonesia.